Effect of some phytogenic additives as dietary supplements on performance, egg quality, serum biochemical parameters and oxidative status in laying hens - ALAGAWANY, MAHMOUD; EL-HACK, MOHAMED E ABD; SAEED, MUHAMMAD; ARAIN, MUHAMMAD A; BHUTTO, ZOHAIB A; FAZLANI, SARFRAZ A; BROHI, SARFRAZ A; ARIF, MUHAMMAD (The Indian Journal of Animal Sciences, 2017)
The aim of the present study was to investigate the impact of some phytogenic feed additives on performance and quality of eggs as well as blood constituents and antioxidant indices in laying hens. Hi-sex Brown laying hens (72) were assigned to 3 dietary treatments (6 replications of 4 hens in a group) and were fed the basal diet or diets supplemented with 0.9% of rosemary and thyme herbs till 52 wk-old. There were no differences in feed intake and egg weight due to herbs addition. Feed conversion ratio, egg production and egg output improved with herbal plants supplementation compared to control. Egg quality traits were significantly affected by herbs supplementation.There were significant differences among the different experimental groups and control on all serum constituents studied except total protein, albumin and HDL-cholesterol. In comparison to control, the diet enriched with rosemary herb significantly lowered serum triglyceride, cholesterol and LDL-cholesterol concentrations. Super oxide dismutase (SOD) activity was statistically improved in phytogenic additive groups, and was maximized (277 U/ml) with dietary thyme. While, malonaldehyde (MDA) level decreased compared to control. It can be concluded that thyme and rosemary supplemented up to 0.9% can be used as effective natural feed additives in layer diets to improve performance, immune response and antioxidant status.